2017
DOI: 10.1155/2017/8576404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Rays onSophora davidiiand Detection of DNA Polymorphism through ISSR Marker

Abstract: Sophora davidii (Franch.) Kom. ex Pavol is an important medicinal plant and a feeding scrub with ecological value. The effects of different gamma irradiation doses (20–140 Kr) on seed germination and seedling morphology were investigated in S. davidii, and intersimple sequence repeat (ISSR) markers were used to identify the DNA polymorphism among mutants. Significant variations were observed for seed germination, stem diameter, and number of branches per plant. The improved agronomic traits, such as stem diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
4
14
1
Order By: Relevance
“…It was revealed that DNA changes had occurred in these materials and the dendrogram, showing the formation of five main groups of mutants, and that indicated the effects of different irradiation dosages on seedlings are far from each other. This result was in accordance with the studies on Sophora davidii (Wang et al, 2017), lily (Xi et al, 2012) and banana (Khan, 2011). Also, there is a genetic gap between dwarfing plants and other types of variation, and it can be concluded that the dwarfing plants have a genetic level change that is of great significance for obtaining dwarfing varieties of ground-grown chrysanthemum and the mutants were successfully identified through ISSR analysis.…”
Section: Discussionsupporting
confidence: 92%
“…It was revealed that DNA changes had occurred in these materials and the dendrogram, showing the formation of five main groups of mutants, and that indicated the effects of different irradiation dosages on seedlings are far from each other. This result was in accordance with the studies on Sophora davidii (Wang et al, 2017), lily (Xi et al, 2012) and banana (Khan, 2011). Also, there is a genetic gap between dwarfing plants and other types of variation, and it can be concluded that the dwarfing plants have a genetic level change that is of great significance for obtaining dwarfing varieties of ground-grown chrysanthemum and the mutants were successfully identified through ISSR analysis.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that the mutants and their parent and the check possess a moderate polymorphism as well as revealed by Xi et al (2012) and Wang et al (2017) who also detected a moderate polymorphism among gamma rayinduced mutants. The appearance or disappearance of bands as specific for γ-ray induced mutants is may be attributed to DNA structural rearrangements caused by different types of DNA damages (Selvi et al, 2007 andMejri et al, 2012).…”
Section: C-issr Marker Analysissupporting
confidence: 64%
“…Detection of genetic diversity using molecular markers of ISSR has been carried out in several previous studies (Wang et al, 2012;Patel et al, 2015;Taheri et al, 2013;Wang et al, 2017). Single nucleotide polymorphisms are the genetic markers of choice in various genetic, ecological and evolutionary studies (Tang et al 2016).…”
Section: Analysis Of Issr Molecular Markersmentioning
confidence: 99%
“…Besides plant material, primary selection is also very important. Wang et al (2017) in his research on the Sophora davidii plant stated that the induction of gamma radiation was able to produce genetic diversity between 75-86% based on the ISSR marker. Another study conducted by Taheri et al (2013) on Curcuma alismatifolia plants based on ISSR analysis results of gamma-ray irradiation obtained diversity between 27-100%.…”
Section: Analysis Of Issr Molecular Markersmentioning
confidence: 99%